Kepastian Pengaturan Label Halal Produk Siap Saji Non Kemasan pada Bisnis Online bagi Masyarakat dalam Era Pandemi Covid-19 - Siti Nur Azizah (Palita: Journal of Social Religion Research, 2021)
Abstract[English]:This paper aims to show the implications of the Covid-19 Pandemic on the online business of non-packaged ready-to-eat products, especially related to aspects of the inclusion of halal labels. Currently, most online shops, online trading groups, e-commerce platforms, and e-business models in the online business of non-packaged ready-to-eat products do not yet include a halal label, even though Law No. 33 of 2014 concerning Halal Product Guarantee has required it. This is of course a problem considering the halal aspect of the product is one of the important issues for Indonesian consumers, who are mostly Muslim. At the same time, there are still people who think that even without a halal label, it is not necessarily a product that is haram. Halal labels seem to not only try to guarantee substances but also cover the production process from start to finish, the use of production tools that should not mix between halal and non-halal products, as well as their storage. In a pandemic condition where the online shopping process is an important alternative that allows without direct interaction, making awareness of the halal label as an indicator of guarantee becomes important for producers to prepare. This means that business actors must really be able to provide such guarantees even without direct interaction. In order to ensure the halal aspect of a product for consumers, of course, it requires the synergy of all parties in the implementation and supervision as well as the implementation of the sanctions. In the end, the legal approach to small business actors still requires massive socialization in the perspective of education and persuasion by involving online business application owners in order to guarantee the halalness of a product that guarantees the right of consumers to obtain halal products even though accessing through online mechanisms.Abstrak[Indonesia]: Tulisan ini bertujuan untuk menunjukkan implikasi Pandemi Covid-19 terhadap bisnis online produk siap saji non kemasan terutama terkait dengan aspek pencantuman label halal. Dewasa ini Kebanyakan online shop, grup dagang online, platform e-commerce, dan model e-business dalam bisnis online produk siap saji non kemasan belum mencantumkan label halal, kendati Undang-Undang No 33 Tahun 2014 tentang Jaminan Produk Halal telah mewajibkannya. Hal ini tentu saja menjadi suatu permasalahan mengingat aspek kehalalan produk merupakan salah satu isu penting bagi konsumen Indonesia yang sebagian besar Muslim. Pada saat bersamaan masih ada masyarakat beranggapan bahwa meski tanpa label halal, belum tentu suatu produk itu haram. Label halal nampaknya tidak saja berupaya menjamin zat saja tetapi juga melingkupi proses produksi dari awal sampai akhir, penggunaan alat-alat produksi yang tidak boleh bercampur antara produk yang halal dan tidak halal, demikian pula dengan penyimpanannya. Dalam kondisi pandemi dimana proses belanja online menjadi salah satu alternatif penting yang memungkinkan tanpa interaksi langsung menjadikan kesadaran akan label halal sebagai suatu indikator jaminan menjadi penting untuk disipakan oleh para produsen. Artinya para pelaku usaha, harus betul-betul dapat memberikan jaminan tersebut meski tanpa interaksi langsung. Guna memastikan aspek halal suatu produk bagi konsumen tentu memerlukan sinergi semua pihak dalam pelaksanaan dan pengawasan serta penerapan sangsinya. Pada akhirnya, pendekatan hukum kepada pelaku usaha kecil masih memerlukan sosialisasi yang massif dalam perspektif edukasi dan persuasi dengan melibatkan pemilik aplikasi bisnis online guna memberikan jaminan kehalalan suatu produk yang menjamin hak konsumen untuk mendapatkan produk halal meski mengakses melalui mekanisme online.